Disfunción familiar y el trastorno disocial en los estudiantes de la Unidad Educativa Municipal ciudad de Quevedo - Costavalo Muñoz, Sandra Isabel (2019)
The family environment has a decisive influence on the personality of a human being, where relationships with household members determine the effects, attitudes and values that the child assimilates from birth. Considering that today there are many factors that drain within the home which puts the emotional and psychological environment of the students at risk, this is why the current research has as its main objective to determine the incidence of family dysfunction and the disorder Disocial in the students of the Municipal Educational Unit "Ciudad de Quevedo". In the present investigation that was elaborated with the programmed subject that was realized in the Municipal Educational Unit "City of Quevedo" of the city of Quevedo, province of Los Ríos, that had like objective of corresponding study in a population of students that its amount makes a sum of 570 students between basic and baccalaureate. According to data that was collected by the DECE department of the educational unit if there have been many cases of disruptive behavior in the classroom that are provided as bad behavior in the institution; this is why this research is intended to know what were the causes of this disorder and who intervened for these types of problems. This research also analyzed how it affects the problems that were prevailing in the operation on the family society of how they were related to the lack of love, affection and education, and also in abundance confidence can harm the proper or correct coexistence which can affect the end of student behavior.